Thank you for slowing down: Slow down. Sit still. Clear your mind. At the Urban Meditation Time Machine - Pappas, Stephen Nicholas (My University, 2017)
This research report intends to illuminate the effect of how we can slow down, clear our minds and come to a complete standstill in extremely fast cities. To apprehend these effects the investigation focuses contextually, around the eastern edge of Newtown Johannesburg. This site is juxtaposed within the intensity of major transport nodes. We are living in a world that is accelerating at a frightening pace, and people are not keeping up - there is very little time in one’s day to escape the rapidity, acquire peace of mind and absorb the present moment. This research report acts as a precedent for how future utopian cities can host a space that encourages a meditative-lifestyle of slowing down. I unfold three theories to help support my investigation; Lieven de Cauter’s theory on capsularisation tells us how man has turned to ‘hyper-individualisation’, closing himself off from the world and creating social barriers. The second theory I look at is non-places by Marc Augé who talks about the in between places we pass through such as petrol stations, bus stops, terminals, etcetera, and how these transient spaces have become more meaningful because one is spending more time in them due to technological advancement. I label these as delayed spaces in my thesis which is the third theory I look at by Fardjadi and Mostafavi. I engage with these last two theories by doing an evaluation on them; these include multi-faith spaces, petrol stations, bus stops, terminals and launderettes. I do so because these are spaces where people slow down and pass through within an ordinary day. I suggest how these activities, that are normally considered mundane, can be transcended through different opportunities to slow down through a meditative life-style. Within each evaluation particular lessons are acquired that are integrated in the overall building design. At one point in the research report I take a time-out from the design process to question the value of slow architecture. Much of the working world as well as universities have an uncomfortable urgency when it comes to design. There is no time to reflect on mistakes made or gain perspective on the process which leads to quick decisions without much thought, and often lack in creative depth or meaning. I touch on my own design process and thinking as an example to explain why it is important to slow down and review what has been done to be able to move forward with clear direction. In terms of the architecture for my research report, two specific concepts are unravelled; the first one is movement - how one approaches the building as well as the circulation within it. I used the labyrinth and the notion of time-frames to support this idea of slowing down from speed to stillness which determined my program. The second concept is the ‘consciousness capsules’ which host the main meditative spaces and activities in the building. These activities make up the program and they include a multi-functional gathering space, a communal library to learn about meditation and its philosophy, hand-craft workshops (such as painting, quilting and basket weaving), meditation rooms, collective yoga, a dormitory, and finally a public garden terrace at the very top accompanied by a walking labyrinth. The whole journey through the building portrays a ‘stairway to heaven’ and provides an overview of the city that allows for one to escape the bustle and re-collect ones’ thoughts and immerse in the present moment - as nothing is more urgent today than slowing down.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Urban renewal--South Africa--Johannesburg; City planning--South Africa--Johannesburg; Public spaces--Social aspects--South Africa--Johannesburg